Optimization of geometrical parameter for V-type alpha Stirling engine based on dimensionless analysis - Varit Senviboon; Banterng Silpsakoolsook; Sutapat Kwankaomeng (My University, 2018)
This paper aims to study the effect of mechanism and geometrical parameters on the shaft work of alpha-type Stirling engine with V-cylinder arrangement and find the appropriate value of geometrical parameters to get the maximum value of shaft work output. The equation of motions of both expansion and compression pistons and the variations of volumes and pressures inside the cylinders are expressed in dimensionless forms. Schmidt analysis and Senft’s shaft work theory are used to build dimensionless thermodynamic models in order to derive dimensionless shaft work and optimal geometrical parameters for achieving the maximum efficiency
Keywords: Dimensionless quantity; Advanced Thermodynamic Systems and Engines